Generation of Three Dimensions Image of Tumor Regions in Sagittal and Coronal Orientations MRI of Brain - Saadoon Abdoon, Rabab (Journal of Kufa-Physics, 2018)
The anatomy information that provided by MRI made it an indispensable tool for diagnosis purposes in present. There are three orientations of acquiring the sliced images of brain in MRI, which are: sagittal; coronal and axial. So it is a vital task to find out an effective and adequate technique for processing and segmenting MRI sliced images of the three orientations modalities to detect and extract tumors in these images.In this work, a simple and effective technique that, it adequate to segment sagittal and coronal orientations, is proposed. This technique is one of the enhancement methods that based on the histogram of the image. Besides, morphological operations were proposed to isolate and extract the tumor regions adequately from successive sliced MRI images of brain of a patient suffer from brain tumor, to utilize them later in generating three dimensions image of the extracted tumor. In addition, the location of the tumor was determined andhold completely within the contouring map of the patient’s head for the two adopted orientations. The importance of this work involving that,this process gives the surgeon a better view seen for the tumor from different orientations to enable him to find out an optimal path to reach the tumor with minimum damage of the surrounding tissues. This work was achieved by the aid of Mat Lab programming system..